2020
DOI: 10.1021/acsabm.0c00163
|View full text |Cite
|
Sign up to set email alerts
|

Colistin-Loaded Polydopamine Nanospheres Uniformly Decorated with Silver Nanodots: A Nanohybrid Platform with Improved Antibacterial and Antibiofilm Performance

Abstract: Bacterial infections, especially chronic infections caused by bacterial biofilms, have become a worldwide threat to public health. Encouragingly, the synergistic actions of two or more antibacterial drugs have been proven to be effective in treating refractory bacterial infections. Herein, we fabricated a robust antibacterial nanohybrid, the colistin-loaded polydopamine nanospheres (PDA NSs) decorated uniformly with small silver nanodots (u-CPSs), and the u-CPSs could realize synergistic bactericidal performan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 66 publications
1
29
0
Order By: Relevance
“…For example, lipid-based nanostructures encapsulating Col were proposed by several authors [ 21 , 22 , 23 , 24 , 25 ] and different chitosan-based nanocarriers have been shown to improve Col antimicrobial activity [ 26 , 27 ]. Moreover, recently Ran HH et al [ 28 ] developed Colistin-loaded polydopamine nanospheres decorated with silver nanodots with improved antimicrobial and antibiofilm activity. In this contest, protein-based polymers such as albumin have been considered as drug carriers due to their non-toxicity, biocompatibility, biodegradability and poor immunogenic properties [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, lipid-based nanostructures encapsulating Col were proposed by several authors [ 21 , 22 , 23 , 24 , 25 ] and different chitosan-based nanocarriers have been shown to improve Col antimicrobial activity [ 26 , 27 ]. Moreover, recently Ran HH et al [ 28 ] developed Colistin-loaded polydopamine nanospheres decorated with silver nanodots with improved antimicrobial and antibiofilm activity. In this contest, protein-based polymers such as albumin have been considered as drug carriers due to their non-toxicity, biocompatibility, biodegradability and poor immunogenic properties [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is widely recognized that the mechanism of employing hyperthermia for killing microorganisms is destroying diverse life-fundamental molecules or structures, including protein denaturation, lipid evaporation, and cell membrane breakage [ 2 , 52 ]. To date, many kinds of PTAs, such as carbon-based nanomaterials [ 53 , 54 ], noble metal nanomaterials [ 55 , 56 ], other metal-containing nanocomposites [ 57 ], and conjugated polymers [ 35 , 36 ], have been used for antimicrobial applications and have established their unique advantages. Moreover, owing to the uneven heat distribution in the bacterial biofilms, it is difficult to completely eradicate the bacteria within the biofilms via PTT alone.…”
Section: Applications Of Low-temperature Pttmentioning
confidence: 99%
“…The synergistic actions of two or more antibacterial drugs as nanohybrids have been established to be effective in the treatment of refractory bacterial infections. The colistin-loaded PDA nanospheres decorated with silver nanodots are reported by Ran et al (2020) to exhibit powerful antibacterial and antibiofilm effects.…”
Section: Cationic Charge Enriched Pda-fabricated Surfaces: Effect On mentioning
confidence: 99%